Ransom slavery along the Ottoman borders : early fifteenth-early eighteenth centuries - Dávid, Géza.; Fodor, Pál. (Ottoman Empire and its heritage ;, 2007)
Notwithstanding the spectacular upswing in the research, there are areas of Ottoman slavery that have still not received the attention they deserve. This volume intends to take a step towards bridging this gap. The twelve studies it contains are organised around connected themes: the hunt for, the trade in and the treatment of captives in the Balkans and in Central Europe. The area under scrutiny is focussed on Hungary, and some other border regions extending from the Crimea to Malta. It offers both an analytic and synthetic approach based on a great deal of so far unpublished Ottoman and European archival material. It not only examines Christian slavery in the Ottoman Empire, but also provides greater insight into the tribulations of Ottoman slaves in the Christian world and sheds light on the devastating effect of captive-related transactions on trade and sometimes on the financial position of whole communities.